Lead-free (Ba, Ca)(Ti, Zr)O3 ceramics within the polymorphic phase region exhibiting large, fatigue-free piezoelectric strains. (5th November 2017) - Chaiyo, Nopsiri; Cann, David P.; Vittayakorn, Naratip
Abstract: Lead-free x BaZrO3 -(0.85- x )BaTiO3 -0.15CaTiO3 ; x = 0.00–0.20 ( x BZ) ceramics were prepared successfully using the conventional solid-state reaction method. Unipolar electric-field-induced strains of the composition x = 0.125 in the polymorphic phase region (PPR) composition show an extraordinarily high normalized piezoelectric coefficient ( d 33 ⁎ ) of 2244 pm/V with relatively low hysteresis at a low electric field of 5 kV/cm, which is higher than that of most reported lead-free ceramics. The PPR composition also exhibits excellent fatigue resistance to bipolar electric cycling with negligible loss of electric-field-induced strain after 10 6 cycles. A two-phase mixture model featuring short-range ordering, which is dispersed in the long-range ferroelectric phase, is proposed to explain the outstanding piezoelectric properties. The reversible electric-field-induced phase transition between the two states is responsible for the large normalized piezoelectric coefficient and fatigue resistance. Under repeated electric cycling, the domains become more dynamic, and the change in domain configuration becomes easier due to decreased energy requirement upon polarization reversal. Furthermore, the ceramic shows single crystal-like behavior characterized by a nearly vertical slope in the polarization hysteresis data, which correlates to the electric field induced transformation from a multi-domain state to a single-domain state. This environmentally benign lead-free ceramic, with outstanding properties, has great potential use for highly responsive and reliable actuators. Graphical abstract: Highlights: Large d 33 ⁎ value greater than 2000 pm/V was observed in BaZrO3 -CaTiO3 -BaTiO3 system. Intrinsic fatigue resistance to bipolar electric cycling was also observed in the PPBs composition A two-phase mixture model is proposed to explain the large piezoelectric response.